Firm expectations and economic activity - Zeno Enders; Franziska Hünnekes; Gernot Müller (Center for Economic Studies and ifo Institute (CESifo), 2019)
We assess how survey expectations impact production and pricing decisions on the basis of a large panel of German firms. We identify the causal effect of expectations by matching firms with the same fundamentals but different views about the future. The probability to raise (lower) production is 15 percentage points higher for optimistic (pessimistic) firms than for neutral firms. Optimistic firms are also more likely to raise prices. In a second step, we find optimism and pessimism to matter even if they turn out to be incorrect ex-post. Lastly, we quantify the contribution of incorrect optimism and pessimism to aggregate fluctuations.
Keywords: E32; D84; E71; 330